Relationships between COE prices, property prices and stock market performance. - Chua, Kwai Fong. (2013)
As the economy grows in affluence, Singaporeans look to the different avenues of investment for their excess cash. Out of the various alternatives, stock or shares, property and cars have received keen attention from investors.